The role of nocturnal delivery and delivery during the holiday period in Finland on obstetric anal sphincter rupture rates- a population based observational study - Vehviläinen-Julkunen Katri; Räisänen Sari; Gissler Mika; Heinonen Seppo (BMC Research Notes, 2010)
Abstract Background Obstetric anal sphincter rupture (OASR) is a serious complication of delivery, which frequently results in faecal incontinence despite primary repair and has serious implications for women's health. The objective of this study was to assess whether human factors, workload and staffing at night, at weekends and during holidays has an effect on the increasing OASR rates among all singleton vaginal deliveries (n = 514,741) having occurred between 1997 and 2007 in Finland. Women (n = 2,849) with OASR were compared in terms of possible risk factors to women without OASR using stepwise logistic regression analysis. Findings In Finland, the increase in OASR rate is striking, from 0.2% in 1997 to 0.9% in 2007. OASR rates varied from 0.49% to 0.58% (≤ 0.001) according to the time of day, and were lowest at night. After adjustment for patient-mix and the use of interventions, the risk of OASR was 11% lower (95% CI 3-18%) at night and 15% lower (95% CI 3-26%) in July - the main holiday month. Only 14% of the increased OASR risk during the day time (8-23.59) was attributable to vacuum assistance and birth weight, whereas the holiday period had no effect. Conclusions Decreased OASR rates at night and in July suggest that human factors such as decreased alertness due to fatigue or hospitals' administrative factors such as workload and staffing did not increase the rates of OASR.